2010
DOI: 10.1142/s0192415x10007749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbal Medicinal Formulas on Suppressing Viral Replication and Modulating Immune Responses

Abstract: The Chinese medicinal herbs Radix Isatidis and Viola yedoensis Makino have been suggested to possess antiviral activity. This study tests whether these and other Chinese and Western herbal medicinal formulas can modulate the immune functions involving virus-suppression in BALB/c mouse. We first confirmed the extract from Viola yedoensis Makino, but not from Radix Isatidis, the traditional Chinese medicine (TCM) formula Chui-Uren-Chien (CUC), or a Western homeopathic medicinal drink Método Canova, could inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…This formulation has a long history of use for alleviation of blood toxicity and sleep disturbance. It is also used to relieve hot flushes and lower serum levels of inflammatory cytokines, IL-6, IL-8, and macrophage protein 1- β [71, 72]. …”
Section: Resultsmentioning
confidence: 99%
“…This formulation has a long history of use for alleviation of blood toxicity and sleep disturbance. It is also used to relieve hot flushes and lower serum levels of inflammatory cytokines, IL-6, IL-8, and macrophage protein 1- β [71, 72]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, gallnut extracts have also been shown to reduce the expression of proinflammation cytokines such as TNF- α , IL-6, and IL-1 β [47]. One study of rats injected with Radix isatidis oral liquid or with 5-fluorouracil reported that the ratio of chemotactic factors in the blood plasma of both groups was higher after 8 weeks [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Compared with oseltamivir phosphate, which has been widely used against influenza virus infection worldwide, Lianhuaqingwen capsule can more significantly improve the symptoms that individuals experience with influenza A virus infection (Duan et al, ; Zhao, Yang, Lv, & Wei, ). With the improvement of screening and separation techniques, it has become an important way to find the ingredients with antiviral activity in traditional Chinese medicine (Ball et al, ; Chang, Huang, Lin, Tsou, & Lin, ; Ikemoto et al, ; Liao et al, ; Lin et al, ; Ma et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%